Mild exercise in female subjects impairs complex learning independent of hydration status and emotion - Turner, Joshua M.; Marsteller, Douglas A.; Luxkaranayagam, Anita T.; Fletcher, John M.; Stachenfeld, Nina S. (Physiology & behavior, 2017)
Depending on type, intensity and duration, exercise can have both beneficial and detrimental effects on cognitive function. The impact of exercise on learning and memory is also sensitive to hydration status, so we hypothesized that mild hypohydration induced with exercise, will adversely impact executive and complex memory function tasks and that these changes in cognitive function are independent of changes in emotion. Using a cross over design, on separate days 11 women exercised on a recumbent bicycle. On day 1, women exercised to 1.5% hypohydration at 34°C, and <10% rh, on day 2, water loss from sweating was replaced by drinking water (euhydration). Pre- and post-euhydration and hypohydration, subjects underwent computer based cognitive tasks (simple, learning, memory, executive function) and visual analog testing to determine emotion. Exercise increased Groton Maze Learning Test errors within both conditions: [Pre: 41.5±11.8, Post: 46.8±12.4, and Pre: 41.9±9.2, Post: 46.5±12.9, hypohydrated and euhydrated, respectively, Pre vs Post, ANOVA, time effect, P=0.007], a test of acquisition, storage, and use of new knowledge. None of the measures of emotion were affected by exercise under either hydration condition. A bout of mild aerobic exercise compromised performance on a complex learning and memory task, but this change was unaffected by hydration status or emotion. •Exercise can impair executive function.•Exercise effects on cognitive function are independent of emotion.•Determination of hydration with Potters scale•Mild exercise effects on cognitive function are independent of hydration status.